Y - 1 = 4y - 2/3. Move the ys over to one side, +4y crosses over to become -4y,
and -1 crosses over the right side to become +1.
y -4y = -2/3 + 1
-3y = 1 - 2/3
-3y = 1/3 Divide both sides by -3.
-3y/-3 = (1/3) / -3.
y = 1/3 * -1/3
y = - 1/9
It can't be factorized it has no common factors no factor of 4 will go easily into 9
3x+2(3x-3)=2
9x-6=2
9x=8
X=8/9
4 + 10 = 2 x 2 + 2 x 5 = 2 x (2 + 5)
The expression which is equivalent to the given expression as in the task content is; 1.5 raised to the fifteenth power divided by 0.7 raised to the twelfth power.
<h3>What is the expression which is equivalent to the given expression?</h3>
According to the task content, it follows that the expression given is;
(1.5⁵/0.7⁴)³
= 1.5^(3×5) /0.7^(4×3)
= 1.5¹⁵/0.7¹².
Hence, the expression which is equivalent is; 1.5 raised to the fifteenth power divided by 0.7 raised to the twelfth power.
Read more on exponents;
brainly.com/question/847241
#SPJ1